1998
DOI: 10.1042/bj3300651
|View full text |Cite
|
Sign up to set email alerts
|

Heparin inhibits Ca2+/calmodulin-dependent kinase II activation and c-fos induction in mesangial cells

Abstract: Like vascular smooth-muscle cells, rat mesangial cells (RMCs) display an anti-mitogenic response to heparin. In particular, heparin partially suppresses the ability of quiescent RMCs to enter the cell cycle and induce c-fos expression. When the mitogenic stimulus is serum, phorbol ester or platelet-derived growth factor, this response appears to result from the ability of heparin to suppress activation of the extracellular-signal-regulated kinase family of mitogen-activated protein kinases. However, we have al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 50 publications
5
32
1
Order By: Relevance
“…25) However, our results in rat hepatocytes suggested that the heparin-stimulated release of HTGL activity was associated with the activation of the intracellular Ca 2ϩ , calmodulin-and CaMK-IIsensitive process. Moreover, the CaMK-II activity in the hepatocytes incubated with heparin was seen to markedly increase.…”
Section: Discussioncontrasting
confidence: 45%
“…25) However, our results in rat hepatocytes suggested that the heparin-stimulated release of HTGL activity was associated with the activation of the intracellular Ca 2ϩ , calmodulin-and CaMK-IIsensitive process. Moreover, the CaMK-II activity in the hepatocytes incubated with heparin was seen to markedly increase.…”
Section: Discussioncontrasting
confidence: 45%
“…A recent report by Miralem et al 22 has also shown that heparin inhibits CaM kinase II activity in mesangial cells, which like VSMC are sensitive to the antiproliferative effects of heparin. In the study reported here we provide significant insight into the molecular mechanism of action of heparin.…”
Section: Discussionmentioning
confidence: 99%
“…7,22 It is important to note that most of the studies establishing heparin as a pharmacological inhibitor of Ca 2ϩ channels have been performed using permeabilized cells. 19 we reasoned that CaM kinase II may be a target of heparin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the selective MLCK inhibitor, ML-7 (Saitoh et al, 1987) is a very poor inhibitor of CaMK II (Miralem and Templeton, 1998), and the selective CaMK II & IV inhibitor, KN-62, has a very low affinity for MLCK (Tokumitsu et al, 1990;Davies et al, 2000), our results suggest that both MLCK and CaM kinases II and/or IV, might contribute to the iso-volumetric length change in RAPHCs. Thus, we sought to determine if these two Ca 2+ /CaM-dependent pathways act in parallel or series.…”
Section: Are the Effects Of Mlck And Camk Inhibitors Additive?mentioning
confidence: 70%